Suicide‐specific mortality among patients with treatment‐resistant major depressive disorder, major depressive disorder with prior suicidal ideation or suicide attempts, or major depressive disorder alone - David M. Kern; Carla M. Canuso; Ella Daly; Jonathan C. Johnson; Dong Jing Fu; Teodora Doherty; Cori Blauer‐Peterson; M. Soledad Cepeda (Brain and Behavior, 2023)
Abstract Background The impact of treatment‐resistant depression (TRD) or prior suicidal ideation/suicide attempt (SI/SA) on mortality by suicide among patients with major depressive disorder (MDD) is not well known. This retrospective, observational, descriptive cohort study characterized real‐world rates of suicide‐specific mortality among patients with MDD with or without TRD or SI/SA. Methods Adult patients with MDD among commercially insured and Medicare enrollees in Optum Research Database were included and assigned to three cohorts: those with treatment‐resistant MDD (TRD), those with MDD and SI/SA (MDD+SI/SA), and those with MDD without TRD or SI/SA (MDD alone). Suicide‐specific mortality was obtained from the National Death Index. The effects of demographic characteristics and SI/SA in the year prior to the end of observation on suicide‐specific mortality were assessed. Results For the 139,753 TRD, 85,602 MDD+SI/SA, and 572,098 MDD alone cohort patients, mean age ranged from 55 to 59 years and the majority were female. At baseline, anxiety disorders were present in 53.92%, 44.11%, and 21.72% of patients with TRD, MDD+SI/SA, and MDD alone, respectively. Suicide‐mortality rates in the three cohorts were 0.14/100 person‐years for TRD, 0.27/100 person‐years for MDD+SI/SA, and 0.04/100 person‐years for MDD alone. SI/SA during the year prior to the end of observation, younger age, and male sex were associated with increased suicide risk. Conclusions Patients with TRD and MDD+SI/SA have a heightened risk of mortality by suicide compared with patients with MDD alone. Suicide rates were higher in patients with recent history versus older or no history of SI/SA, men versus women, and those of young age versus older age.